CONSTRUCTION STAKEHOLDERS’ PERSPECTIVE ON EXTERNAL RELATED RISK FACTORS INFLUENCING CONSTRUCTION PROJECT PERFORMANCE - ABDARAHIM SALEM; Eric SIMPEH; Julius Fapohunda (Journal of Construction Project Management and Innovation)
Abstract